Caretaker conventions in Australasia: minding the shop for government - Tiernan, Anne (ANU Press, 2007)
In this monograph, Anne Tiernan and Jennifer Menzies capably chart the often hazardous terrain of the 'caretaker period' that ensues from the time an election is called until a new government is formed. This is a landscape fraught with political and administrative dangers - particularly for public servants who are required to 'mind the shop' and keep the basic machinery of government going. The conventions represent an historical accretion of custom, practice and rules, often leavened with uncertainty. In tackling their subject, Tiernan and Menzies draw upon their shared past experiences as public servants and ministerial 'staffers' as well as the highest standards of academic scholarship - this is a 'must read' for politicians, public servants and students of government.